ANALISIS PENGELOLAAN MODAL KERJA DALAM MENINGKATKAN PROFITABILITAS PADA KOPERASI UNIT DESA (KUD) KOTO BARU SOLOK SUMBAR - Suniya Juwita; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The objective of this study was to identify and evaluate the role that working capital management had in boosting the profitability of Koto Baru Solok-Sumbar Village Unit Cooperative (KUD). Quantitative descriptive data types are used in this investigation. Both primary and secondary data were gathered via interviews and financial report data from the Village Unit Cooperative (KUD) Koto Baru Solok-West Sumatra, respectively. First, the management of working capital to liquidity is a result of this studyas measured by the current ratio in a liquid state, but the cash ratio fluctuates, so it is not yet effective. In the cash ratio, this is caused by the amount of cash that is not good at guaranteeing current debt. Second, the management of working capital on Profitability as measured by ROI and ROE shows that it has not been effective which is still below the standards of Indonesian Cooperatives and SMEs, this is due to asset revaluation, a decrease in cooperative consumers and customers. This shows that the cooperative has not been able to manage its assets and capital, so that the profit generated is not optimal. Keywords: Working capital, Liquidity, and Profitability